Measurement of the W+W- cross section in pp collisions at √s = 7 TeV and limits on anomalous WWγ and WWZ couplings - Chatrchyan, S; Chatrchyan, S; Khachatryan, V; Khachatryan, V; Sirunyan, A; Sirunyan, A; Tumasyan, A; Tumasyan, A; Adam, W; Adam, W; Bergauer, T; Bergauer, T; et al. (2013)
A measurement of W+W- production in pp collisions at √s = 7 TeV is presented. The data were collected with the CMS detector at the LHC, and correspond to an integrated luminosity of 4.92±0.11 fb-1. The W+W- candidates consist of two oppositely charged leptons, electrons or muons, accompanied by large missing transverse energy. The W+W- production cross section is measured to be 52.4±2.0 (stat.)±4.5 (syst.)±1.2 (lum.) pb. This measurement is consistent with the standard model prediction of 47.0±2.0 pb at next-to-leading order. Stringent limits on the WWγ and WWZ anomalous triple gauge-boson couplings are set. © 2013 CERN for the benefit of the CMS collaboration.